THE CONSTITUENT OF LOVE IN THE SONNETS OF SHAKESPEARE - Bhushan, Vijay; Mishra, M. S. (International Journal of Psychosocial Rehabilitation, 2021)
Love is one of the basic instincts of the human heart. Since times immemorial poets have sung of its joys and sorrows, pleasures and frustrations, and its ecstasies and dejections. Sexual or quixotic obsession can be very well expressed in Love poetry during the Renaissance period, however it could also dole out a range of political, social and religious ends. The present paper explores the origins and development of love element in the Shakespeare’s Sonnets. Shakespeare has made the element of love as the staple of his poetry and plays. In the sonnets he speaks about the various aspects of love. These aspects can be observed in this succinct aphorism of Bacon : “Nuptial love maketh mankind, friendly love perfecteth it; but wanton love corrupteth and ambaseth it.” In his sonnets Shakespeare speaks about various aspects of love